Extension model developed during third phase of JICA project - Giridhar, K; Jayaswal, Jayant (Indian Farming, 2015)
Nearly 95% of all the silk produced in India is multivoltine oriented. To increase the production of bivoltine silk which is superior in quality, efforts have to be made in right earnes, in right measure and in right direction. Besides qualitative improvements on various inputs and services; the important aspect would be to reach out to the beneficiaries with an approach which is complete in all respects and caters to the specific needs to sustain and enlarge bivoltine cocoon production so as to convert these cocoons into quality yarn of international standards.